Decomposition rates of reducing sugars in sticky cotton using NH4OH4, NH4NO3, and saccharomyces cerevisiae - Tabago, Elejiah D. (2002)
The applicability of the sugar decomposition treatments in lowering the level of sugar content in sticky cotton was investigated. The microorganisms present in the cotton were identified and quantified. The sugar decomposition rates using NH4OH, NH4O3, saccharomyces cerevisae (baking yeast) were determined under 'anaerobic' condition. NH4OH and NH4O3 served as nitrogen source for the microorganisms already present in the cotton. Saccharomyces cerevisiae can decompose sugars both under aerobic conditions (via oxidative process) and anaerobic conditions (via fermentative process). Effect of the treatment on the strength and color of the fiber were also evaluated. The study showed that 'anerobic' condition was effective in decomposing sugars in sticky cotton than the aerobic condition at ambient room temperature and humidity. The sugar decomposition rate in cotton under 'anaerobic' condition is apparently first-order reaction kinetics, which indicates that the decomposition was a microbial mediated process attributed to activity of bacteria present in the cotton sample. The findings suggest that the role of bacteria, which was already present in the cotton in heavy growth is more important in the sugar decomposition process.